If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3s(-2s) = 0 Remove parenthesis around (-2s) 3s * -2s = 0 Reorder the terms for easier multiplication: 3 * -2s * s = 0 Multiply 3 * -2 -6s * s = 0 Multiply s * s -6s2 = 0 Solving -6s2 = 0 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Divide each side by '-6'. s2 = 0 Simplifying s2 = 0 Take the square root of each side: s = {0}
| x+1=6x-x^2 | | 12+6x=8x | | 3sx-2s= | | 3=8r+1+2 | | (x^2+8x+17)/(x+2) | | -6w-3=21 | | 20x-21=2x+14 | | 3(4c+1)2c=13 | | 4*8cs+3c=8c | | 14b+5=10b+21 | | 7x+11=-24 | | 5*12/n-3d=12 | | -25d-3.2=74.1 | | -2x+7(1-(-3x))=-19+3x | | 2(10-2b)+b=6 | | 7x+6=6x-2 | | 7x-5x-3=6 | | (-4)+(-6)(+4)-(-1)= | | 3k*t-k=3k | | 3*7+4h=7 | | -2x^2+4=x^2+x-7 | | 2a+a-5=5 | | 0.5x+8=6 | | 4*4-2(-6)(-2)/(15+3*3)=x | | y-60=6(x-10) | | -(6y+5)-(-5y-7)=-6 | | z^2-1000x+60775=0 | | 2x+35/4=5 | | 4x+2*5-3x=1 | | 4*4=x | | 4*4=4*4 | | 13x-2y=-5 |